Investigação da toxicidade, atividade antifúngica e antibiofilme do 2-bromo-N-fenilacetamida - Melo, Thamara Rodrigues de (2021)
Cryptococcosis is a fungal infection caused mainly by the encapsulated yeasts C. neoformans and C. gattii, which can affect the Central Nervous System with severe and fatal evolution. With an increase in the number of immunosuppressed individuals, caused by HIV and by treatment of immunosuppressants, the number of cryptococcosis by C. neoformans has increased. In addition, conventional therapy with antifungals presents difficulties with regard to toxicity and the emergence of resistant strains. In this context, the search for new antifungal substances has been a promising alternative. Acetamides are molecules that have several biological activities. However, there are no reports on the activity of 2-bromo-N-phenylacetamide (A1Br). Thus, the present study aimed to evaluate the antifungal and antibiofilm activity of the A1Br molecule and its toxic effects. A1Br was synthesized and its structure is characterized by infrared and nuclear magnetic resonance of Hydrogen (1H) and Carbon (13C). The software Pass online, Molinspiration, Osiris and Molecular Docking were used for in silico analysis. In in vitro analysis, evaluation of antifungal activity using broth microdilution technique and checkerboard method. the inhibition of biofilm formation by the violet crystal assay. Cytocytoxity was tested against the ABO system erythrocytes. The A1Br molecule, through in silico analysis, has 410 biological activities and good oral bioavailability and risk in mutagenic, tumorigenic and reproductive effects. In molecular docking, it presents binding energy and favorable interactions for adequate anchoring in 6ISJ and 6TZ8 enzymes, being a possible A1Br action site. The A1Br compound promoted antifungal effect with minimal inhibitory concentration (MIC), the MIC50 was 0.25 - 1 μg / mL with fungicidal action. In investigating the mechanism of action, MIC in the presence of sorbitol remained unchanged. In contrast, A1Br MIC increased in the presence of ergosterol, showing a possible mechanism of action on the plasma membrane. In addition, it has good MICx4 antibiofilm activity, with inhibition growth ≥80%. The combinations of A1Br- amphotericin B and A1Br-voriconazole were antagonists. Cytotoxicity analysis shows low toxicity. In the osmotic fragility analysis, it showed a moderate potential for stability and protection against hemolysis. These results suggest that A1Br represents a promising antifungal and antibiofilm activity against Cryptococcus neoformans, due to a mechanism involving the complexation with ergosterol, in addition to presenting low cytotoxicity.